Interactive Storytelling Marketing Communication Strategies in Building Audience Loyalty on Short Video Platforms - Abdul Latief (Jurnal Ragam Pengabdian, 2026)
The rapid proliferation of short video platforms has significantly reshaped marketing communication practices, urging brands to adopt interactive and narrative-based strategies to capture attention and foster sustained audience relationships within highly competitive digital environments. However, empirical evidence examining how interactive storytelling contributes to audience loyalty in the context of short-form video remains limited. This study aims to analyze the effect of interactive storytelling marketing communication strategies on audience loyalty, with audience engagement functioning as a mediating variable. A quantitative explanatory approach was employed, utilizing an online survey distributed to 100 active short video platform users domiciled in the Jabodetabek area who had previously engaged with brand storytelling content. Data were analyzed using multiple regression techniques to test the direct and indirect relationships among variables. The results indicate that interactive storytelling has a positive and significant effect on audience loyalty, both directly and indirectly through increased audience engagement. Interactive narrative elements such as participatory content formats, episodic storytelling structures, and embedded calls-to-action significantly enhance emotional involvement and repeat viewing intentions. These findings underscore the strategic importance of integrating interactivity within narrative-based marketing communication to strengthen relational bonds with digital audiences. The study offers theoretical novelty by synthesizing narrative engagement and relationship marketing frameworks within the short video ecosystem and provides practical implications for brands in designing data-driven interactive storytelling strategies to cultivate long-term audience loyalty.